A simplified strategic management model for higher education institutions in India. (28th August 2019) - Sawhney, Sahil; Gupta, Ankur; Kumar, Kulwant
The Indian Higher Education (IHE) sector which is currently at an inflection point in the face of critical challenges, presents the ideal scenario for adopting strategic management to ensure competitiveness and continuity. While few researches have strongly advocated the adoption of strategic management in IHE, its prevalence remains abysmally low. Moreover, all the existing strategic frameworks have been conceptualised primarily for business organisations, requiring rich resources and high intellectual capacity to implement. Clearly, a simplified strategic management model customised to the Indian context along with tools and processes which support institutions in seamlessly adopting strategic management are required. We propose a simplified strategic management model (SSMM) with five defining elements, which are adapted to the Indian context. SSMM is implementation-oriented and follows a check-list-based approach to strategic management implementation. Each element of the SSMM has multiple defined maturity levels, includes a seven-step process model for effective implementation, integrates supporting checklists, documentation templates and the use of an innovative quality benchmarking tool to track progress. It is the first instance of a proposed strategic management model for the Indian Higher Education space.